2022
DOI: 10.3389/fcell.2022.918080
|View full text |Cite
|
Sign up to set email alerts
|

Parental obesity-induced changes in developmental programming

Abstract: Many studies support the link between parental obesity and the predisposition to develop adult-onset metabolic syndromes that include obesity, high blood pressure, dyslipidemia, insulin resistance, and diabetes in the offspring. As the prevalence of obesity increases in persons of childbearing age, so does metabolic syndrome in their descendants. Understanding how parental obesity alters metabolic programs in the progeny, predisposing them to adult-onset metabolic syndrome, is key to breaking this cycle. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 228 publications
0
3
0
Order By: Relevance
“…There is a growing awareness that parental obesity may lead to adverse long‐term health consequences for subsequent generations. Both epidemiological and animal studies have provided evidence suggesting that either maternal or paternal obesity independently increases the risk of obesity, metabolic disorders, and mental health impairments in offspring 3–5 . A recent meta‐analysis of observational human studies indicated that specifically paternal obesity, rather than overweight, was significantly associated with mental disorders in offspring, such as anxiety, attention‐deficit/hyperactivity disorder (ADHD), and autism spectrum disorder (ASD) 5 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing awareness that parental obesity may lead to adverse long‐term health consequences for subsequent generations. Both epidemiological and animal studies have provided evidence suggesting that either maternal or paternal obesity independently increases the risk of obesity, metabolic disorders, and mental health impairments in offspring 3–5 . A recent meta‐analysis of observational human studies indicated that specifically paternal obesity, rather than overweight, was significantly associated with mental disorders in offspring, such as anxiety, attention‐deficit/hyperactivity disorder (ADHD), and autism spectrum disorder (ASD) 5 .…”
Section: Figurementioning
confidence: 99%
“…Both epidemiological and animal studies have provided evidence suggesting that either maternal or paternal obesity independently increases the risk of obesity, metabolic disorders, and mental health impairments in offspring. [3][4][5] A recent meta-analysis of observational human studies indicated that specifically paternal obesity, rather than overweight, was significantly associated with mental disorders in offspring, such as anxiety, attention-deficit/hyperactivity disorder (ADHD), and autism spectrum disorder (ASD). 5 However, establishing a casual link between parental obesity and neurocognitive development in offspring has been challenging in human studies, primarily due to the confounding effects of genetic factors and postnatal environment.…”
Section: E D I T O R I a L How Can Paternal Obesity Impair Memory Pro...mentioning
confidence: 99%
“…The liver exerts various vital activities spanning from digestive, metabolic, immunological, and purificatory physiological functions but has limited capacities to deal with the enormous increase of calories provided by food, soft drinks, and alcoholic beverages and with other noxious agents [2] . The ensuing health risks may particularly occur within families, given that parental obesity alters metabolic programs in the progeny, predisposing them to adult-onset metabolic syndrome [3] .…”
Section: Contextmentioning
confidence: 99%
“…Developmental origins of health and disease hypothesis propose a connection between the periconceptual, fetal, and early infant stages of life and the sustained development of metabolic disorders [1,2]. The risk of developing a disease at any point in one's life is shaped by the interplay between genetics and the cumulative impact of lifestyle and environmental exposures across the lifespan [3].…”
Section: Introductionmentioning
confidence: 99%